Emocje badacza jako "narzędzie" analizy i interpretacji danych. Doświadczenia z badań terenowych w agencjach towarzyskich = Researcher`s emotions as a tool for analisis and interpretation of data. Experiences from fieldwork in escort agencies - Ślęzak, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is the afterthought over the emotions of a researcher appearing while performing ethnographic examination as a consequence of long term contact with the researched ones in their environment. Based on experiences from executing a project concerning the situation of women providing sexual services in escort agencies, the emotions of the researcher appearing at various stages of the research, are presented. There is also some conclusions concerning the role of emotions in the research process.
Keywords: emocje; badacz; proces badawczy